2015
DOI: 10.1166/jbn.2015.2168
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional PLGA Nanobubbles as Theranostic Agents: Combining Doxorubicin and P-gp siRNA Co-Delivery Into Human Breast Cancer Cells and Ultrasound Cellular Imaging

Abstract: Multidrug resistance (MDR) is a major impediment to the success of cancer chemotherapy. One of the effective approaches to overcome MDR is to use nanoparticle-mediated the gene silence of chemotherapeutic export proteins by RNA interference to increase drug accumulation in drug resistant cancer cells. In this work, a new co-delivery system, DOX-PLGA/PEI/P-gp shRNA nanobubbles (NBs) around 327 nm, to overcome doxorubicin (DOX) resistance in MCF-7 human breast cancer was designed and developed. Positively charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Biodegradable, hydrophobic polymers are the most common materials for microsphere design, and they contain a single material,24, 25, 26 such as PLGA, ketal, polylactic acid (PLA), and chitosan microspheres, or a composite material,27, 28, 29 such as PLGA‐PEI microspheres, the characteristics of these microspheres are biocompatibility, security, nontoxicity, and rapid degradation. The other microspheres are mainly loaded with polypeptides and siRNA,30, 31, 32 such as liposome microspheres, and the main features of these microspheres are rapid degradation and absorption by cells through endocytosis, which can contribute to the release of polypeptides and siRNA. Additionally, a category of microspheres acts as the scaffolds of the cell, carrying the functional cell to the infarct site for the myocardial infarction treatment,33, 34 such as superparamagnetic microspheres, and the characteristics of these microspheres are porosity and high adsorption capacity, resulting in stable conjugation with the target cell.…”
Section: Discussionmentioning
confidence: 99%
“…Biodegradable, hydrophobic polymers are the most common materials for microsphere design, and they contain a single material,24, 25, 26 such as PLGA, ketal, polylactic acid (PLA), and chitosan microspheres, or a composite material,27, 28, 29 such as PLGA‐PEI microspheres, the characteristics of these microspheres are biocompatibility, security, nontoxicity, and rapid degradation. The other microspheres are mainly loaded with polypeptides and siRNA,30, 31, 32 such as liposome microspheres, and the main features of these microspheres are rapid degradation and absorption by cells through endocytosis, which can contribute to the release of polypeptides and siRNA. Additionally, a category of microspheres acts as the scaffolds of the cell, carrying the functional cell to the infarct site for the myocardial infarction treatment,33, 34 such as superparamagnetic microspheres, and the characteristics of these microspheres are porosity and high adsorption capacity, resulting in stable conjugation with the target cell.…”
Section: Discussionmentioning
confidence: 99%
“…76 Many studies exploited the feasibility of using nanomedicines to reverse DOX resistance. [76][77][78][79][80][81] For example, Wang et al showed that DOX encapsulated in mesoporous silica nanoparticles (MSNPs) can overcome MCF-7/MDR1 cell resistance to DOX. 79 Unsoy et al synthesized chitosan-coated magnetic nanoparticles for targeted delivery of DOX.…”
Section: Natural Productsmentioning
confidence: 99%
“…4 In recent years, polymer nanoparticles that can be used as drug delivery carriers or nonviral gene vectors have aroused high interest in nanomedicine. 5 Among these molecules, poly(lactideco-glycolic acid) (PLGA) is a biodegradable copolymer that has been approved by the United States Food and Drug Administration (FDA) for utilization as a scaffold in tissue engineering and in various drug or gene delivery systems. 6,7 Via the tricarboxylic acid cycle, the final products of the cellular metabolic conversion of PLGA are water and carbon dioxide, which are nontoxic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Via the tricarboxylic acid cycle, the final products of the cellular metabolic conversion of PLGA are water and carbon dioxide, which are nontoxic molecules. 5 Recently, biodegradable gas-filled nanobubbles (NBs) used as ultrasound (US) agents and fabricated from PLGA (denoted as PLGA NBs) have received widespread attention not only because these molecules can improve US signals but also because they can be used as drug carriers. 8 PLGA, as an NB shell with excellent biocompatibility, biodegradability, and mechanical strength, is preferred and popular for use in molecular imaging.…”
Section: Introductionmentioning
confidence: 99%